2008
DOI: 10.1021/ma702190c
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ethylene-co-propylene macromonomer)s:  Synthesis and Evidence for Starlike Conformations in Dilute Solution

Abstract: By use of two sequential coordination−insertion polymerizations, a series of ethylene-co-propylene-based comb polymers was synthesized. First, poly(ethylene-co-propylene) macromonomers featuring one unsaturated chain end were synthesized using a titanium bis(phenoxyimine) catalyst. The macromonomers were then homopolymerized using a living nickel α-diimine catalyst. The molecular weights and corresponding number of arms for each poly(macromonomer) were determined using size-exclusion chromatography with viscom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 93 publications
0
18
0
1
Order By: Relevance
“…transition metal centers. The development of the d-block chemistry of 4 was pioneered by the groups of Brookhart, 4 Elsevier 5 and Coates, 6 and a broad range of transition metal-BIAN complexes has now been described. 7-10 A focal point of this activity has been the generation of robust, versatile catalysts for olefin polymerization 11 and other important organic transformations.…”
Section: Introductionmentioning
confidence: 99%
“…transition metal centers. The development of the d-block chemistry of 4 was pioneered by the groups of Brookhart, 4 Elsevier 5 and Coates, 6 and a broad range of transition metal-BIAN complexes has now been described. 7-10 A focal point of this activity has been the generation of robust, versatile catalysts for olefin polymerization 11 and other important organic transformations.…”
Section: Introductionmentioning
confidence: 99%
“…193,195 The chain-walking polymerization method has been widely used to adjust the thermal, rheological, and mechanical properties of polymers, specifically for macromolecules formed from a-olefin monomers. [196][197][198][199] In addition, Alamo and coworkers showed that chain-walking polymerization can be utilized to synthesize isotactic polypropylene with regional defects caused by irregularity in distribution or density of methyl groups along polymer chains. 200 They illustrated that at comparable defect density, polypropylenes with such chain-walking defects have lower melting points and much lower degrees of crystallinity than isotactic polypropylenes with regional defects induced by copolymerization with other 1-alkene comonomers.…”
Section: Linear Polymers With Controlled Moderate Degrees Of Branchingmentioning
confidence: 99%
“…were synthesized using “living” olefin polymerization techniques . Coates and co‐workers reported the synthesis of comb POs ( M n = 74–209 kg mol −1 , PDI = 1.51–1.90) via the ‘living” polymerization of poly(ethylene‐co‐propylene) macromonomers catalyzed by a nickel/α‐diimine catalyst. The macromonomers with unsaturated chain ends ( M n = 4.8–23.3 kg mol −1 , PDI = 1.62–1.81) were synthesized by a titanium bis(phenoxyimine) catalyst .…”
Section: Preparation Of Long‐chain‐branched Pos With “Living” Polymermentioning
confidence: 99%
“…Coates and co‐workers reported the synthesis of comb POs ( M n = 74–209 kg mol −1 , PDI = 1.51–1.90) via the ‘living” polymerization of poly(ethylene‐co‐propylene) macromonomers catalyzed by a nickel/α‐diimine catalyst. The macromonomers with unsaturated chain ends ( M n = 4.8–23.3 kg mol −1 , PDI = 1.62–1.81) were synthesized by a titanium bis(phenoxyimine) catalyst . Latter, the same group reported controlled synthesis of syndiotactic PP bottlebrush polymers ( M n = 46–172 kg mol −1 , PDI = 1.21–1.89) via the ring‐opening metathesis polymerization (ROMP) of norbornene‐terminated syndiotactic PP .…”
Section: Preparation Of Long‐chain‐branched Pos With “Living” Polymermentioning
confidence: 99%